2010
DOI: 10.1088/0960-1317/21/1/015016
|View full text |Cite
|
Sign up to set email alerts
|

Self-alignment in the stacking of microchips with mist-induced water droplets

Abstract: This paper reports a novel and versatile water droplet self-alignment technique where the water is delivered in mist form onto the assembly site. The droplet forming process has been carefully investigated using machine vision, where each individual droplet on the microchip surface can be identified and the volume per surface area can be calibrated at a specific time. The result reveals that the volume of water droplets on the assembly surface grows linearly as a function of time. Self-alignment based on the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…The method is built upon the recent efforts on combining robotic microhandling and self-assembly into a hybrid microassembly strategy [3][4][5][6][7], where fast-speed robotic pick-and-place is used for coarse positioning, and high accuracy is reached by capillary self-alignment of a droplet, driven by the capillary force between the die and the receptor site. The capillary force also aids in overcoming the adhesion forces between the die and the gripper, which is a common problem in micromanipulation.…”
Section: Introductionmentioning
confidence: 99%
“…The method is built upon the recent efforts on combining robotic microhandling and self-assembly into a hybrid microassembly strategy [3][4][5][6][7], where fast-speed robotic pick-and-place is used for coarse positioning, and high accuracy is reached by capillary self-alignment of a droplet, driven by the capillary force between the die and the receptor site. The capillary force also aids in overcoming the adhesion forces between the die and the gripper, which is a common problem in micromanipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly technique has been demonstrated for assembly of micro sized components driven by capillary forces [2][3][4][5][6][7], magnetic forces [8] and electrostatic forces [9]. Another promising technique to achieve high alignment accuracy and high speed is hybrid assembly technique, which is proposed by the authors previously [10][11][12][13]. The technique combines the robotic pick-and-place technique and self-assembly technique.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier work [10][11][12][13], we have reported that the hybrid assembly technique can simultaneously achieve the desired performance in both speed and accuracy. However, it has not been proven that the hybrid assembly technique can be used for massively parallel assembly of microchips.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] One key aspect of the technology is a well-designed receptor site where the self-alignment process of the selfassembly will take place. The general rule is that the receptor site should be lyophilic (against the lyophobic background) to the self-alignment medium-the liquid medium between the receptor site and the micropart to be assembled, e.g., hydrophilic receptor site if water is used as the self-alignment medium in air [6][7][8][9][10][11] or oleophilic receptor site if adhesive is used as self-alignment medium in water. [1][2][3][4][5] In air, solid-edges can also be used as the boundary for the self-alignment process.…”
mentioning
confidence: 99%